177k views
4 votes
Xx squared - XY + x squared - xy ​

User TorbenJ
by
5.5k points

2 Answers

4 votes

Answer and Step-by-step explanation:


x^(2) - xy + x^(2) -xy\\\\2x^(2) -2xy

This is the answer.

User MrEyes
by
5.1k points
5 votes

In case your expression is:


x^2\:-\:xy\:+\:x^2\:-\:xy

Solution:

Given the expression


x^2\:-\:xy\:+\:x^2\:-\:xy

Group like terms


x^2\:-\:xy\:+\:x^2\:-\:xy=x^2+x^2-xy-xy

Add similar elements: x²+x² = 2x²


=2x^2-xy-xy

Add similar elements: -xy-xy = -2xy


=2x^2-2xy

Thus,


x^2-xy+x^2-xy=2x^2-2xy

In case your expression is:


\left(xx\right)^2\:-\:xy\:+\:x^2\:-\:xy

Solution:

Given the expression


\left(xx\right)^2\:-\:xy\:+\:x^2\:-\:xy

Group like terms


\left(xx\right)^2\:-\:xy\:+\:x^2\:-\:xy=x^2-xy-xy+\left(xx\right)^2

Add similar elements: -xy-xy = -2xy


=x^2-2xy+\left(xx\right)^2

as (xx)² = x⁴

so
=x^2-2xy+x^4

Therefore, we conclude that:


  • \left(xx\right)^2\:-\:xy\:+\:x^2\:-\:xy=x^2-2xy+x^4
User Zdenek Hatak
by
6.2k points